Hadith #108 - Shama'il Muhammadiyah (Shama'il Muhammadiyah)
“The Prophet (Allah bless him and give him peace) entered Mecca wearing a helmet. He was told: ‘This Ibn Khatal is clinging to the curtains of the Ka’ba so he said: ‘Kill him!'”
Grade:

Hadith #109 - Shama'il Muhammadiyah (Shama'il Muhammadiyah)
“Allah’s Messenger (Allah bless him and give him peace) entered Mecca in the Year of Victory with the helmet on his head. When he took it off, a man came to him and told him: ‘Ibn Khatal is clinging to the curtains of the Ka’ba,’ so he said: ‘Kill him!’ Ibn Shihab said: ‘It has also reached me that Allah’s Messenger (Allah bless him and give him peace) was not in the state of ritual consecration on that day.’”
Grade: